How the Poor Data Privacy Regime Contributes to Misinformation Spread and Democratic Erosion - Unger, Wayne (Science and Technology Law Review, 2021)
Disinformation campaigns reduce trust in democracy, harm democratic institutions, and endanger public health and safety. While disinformation and misinformation are not new, their rapid and widespread dissemination has only recently been made possible by technological developments that enable never-before-seen levels of mass communication and persuasion. Today, a mix of social media, algorithms, personal profiling, and psychology enable a new dimension of political messaging—a dimension that disinformers exploit for their political gain. These enablers share a root cause—the poor data privacy and security regime in the U.S. At its core, democracy requires independent thought, personal autonomy, and trust in democratic institutions. A public that thinks critically and acts independently can check the government’s power and authority. However, when the public is misinformed, it lacks the autonomy to freely elect and check its representatives and the fundamental basis for democracy erodes. This Article addresses a root cause of misinformation dissemination —the absence of strong data privacy protections in the U.S.—and its effects on democracy. This Article explains, from a technological perspective, how personal information is used for personal profiling, and how personal profiling contributes to the mass interpersonal persuasion that disinformation campaigns exploit to advance their political goals.